The last Mimzy [videorecording (DVD)] - Hart, James V.; Skilken, Carol; Rubin, Bruce Joel; Emmerich, Toby; O'Neil, Chris, 1994-; Wryn, Rhiannon Leigh; Richardson, Joely; Hutton, Timothy, 1960-; Wilson, Rainn, 1966-; Hahn, Kathryn, 1974-; Duncan, Michael Clarke; Muro, J. Michael (James Michael), 1966-; et al. (Infinifilm., 2007)
When Emma and Noah find a mysterious box of toys on the beach, strange things start happening. The kids develop special powers and with their parents and teachers, they realize that their mission is far more important than they had ever dreamed.